Investing in Digital Hydrometeorological Data for the Developing World - Thorpe, Alan; Rogers, David P. (World Bank, Washington, DC, 2022)
Addressing many of the global challenges facing humankind requires the availability, access, and use of huge volumes of digital hydrometeorological (hereafter “hydromet”) data needed to inform decision-making to save lives and infrastructure as well as to exploit the associated economic opportunities. The global challenges include the world’s increasing vulnerability to weather, climate, and water stresses, and they are especially acute in developing countries. This technical note outlines the opportunities and requirements for developing countries to be able to benefit from the digital hydromet data revolution.